Técnicas de detección de gonadotropina coriónica equina ''eCG'' como procesos de diagnostico de gestación en yeguas (2020)
Equine chorionic gonadotropin (eCG) is a glycoprotein produced and secreted by the mare's placenta and whose function is to form secondary follicles destined to transform into accessory corpus luteum helping to maintain pregnancy. This hormone can be used as an indicator of early pregnancy in mares, being a possible pregnancy diagnostic technique that complements traditional diagnostic tools (rectal palpation and ultrasound). The objective of the present work is to make a complete literature review on eCG in mares, to identify the diagnostic processes currently used for the detection of the hormone to propose new rapid and accurate diagnostic techniques. A systemic search and literature review was performed through academic search engines and Mendeley was used as bibliographic manager to facilitate the document construction process. It is concluded that the detection of eCG in blood is a complementary method to traditional tests that allows to improve the precision and earlier detection of pregnancy in mares. The ELISA test is the most widely used technique, but it requires laboratory procedures and can give false negatives. Immunochromatography techniques allow rapid diagnostic devices to be developed to detect eCG in blood and urine samples. Nanotechnology is a viable option since it would allow the design of nanoparticle inks for smart tattoos that would allow much easier detection. and quick of the pregnancy in mares.